# Answer to Question #1688 in Calculus for Abhilash

Question #1688

Use logarithmic differentiation to find the derivative of the function.

y = sqrt(x)e^x^2(x^2 + 3)^5

y = sqrt(x)e^x^2(x^2 + 3)^5

Expert's answer

y' = 1/(2√x) * e

= e

= e

^{x^2}(x^{2}+3)^{5}+ 2x√x e^{x^2}(x^{2}+3)^{5}+2x*5* √x e^{x^2}(x^{2}+3)^{4}= e

^{x^2}(x^{2}+3)^{4}(1/(2√x)(x^{2}+3) + 2x^{3}√x + 6x√x + 10x√x) = e^{x^2}(x^{2}+3)^{4}(1/2 * x√x +6x√x + 10x√x + 3/(2√x) + 2x^{3}√x) == e

^{x^2}(x^{2}+3)^{4}(16.5x√x + 3/(2√x) + 2x^{3}√x)Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment